Nintedanib prevented fibrosis progression and lung cancer growth in idiopathic pulmonary fibrosis. Issue 8 (14th September 2018) - Fukunaga, Kentaro; Yokoe, Shinya; Kawashima, Satoru; Uchida, Yasuki; Nakagawa, Hiroaki; Nakano, Yasutaka
Abstract : A 76‐year‐old man with a past history of acute exacerbation (AE) and idiopathic pulmonary fibrosis (IPF) was treated with nintedanib because of decline in his forced vital capacity over time. A new small nodular lesion was visible on a computed tomography scan of the chest before initiation of nintedanib. Disease progression in IPF and change in size of the nodular lesion were not detected during administration of nintedanib. Nine months after starting nintedanib, the patient was diagnosed with acute gangrenous appendicitis, and nintedanib treatment was discontinued. The nodular lesion increased in size four months after the cessation of nintedanib. The nodular lesion was diagnosed as squamous cell carcinoma. In this case, nintedanib inhibited the disease progression of IPF and lung cancer simultaneously. Nintedanib may play an important role in the treatment of IPF‐associated lung cancer. Abstract : Nintedanib prevented progression of IPF and the associated squamous cell carcinoma simultaneously as a result of its diverse mechanisms of action.